Impact Of Nitrogen Fertilizer Management On The Production Of Dry Seeded Paddy (Oryza Sativa L.) In Rainfed Areas Of Telangana (India) (Applied Biological Research, 2020)
The experiment was aimed on to assess the influence of various nitrogen  levels on growth and yield of dry seeded paddy in farmer’s fields. The study  was conducted in three consecutive kharif seasons of 2017-2019 in a  randomized block design with each treatment replicated 5 times. The  treatments comprised of four nitrogen levels i.e. 100, 125, 150 and 175%  recommended N and farmer’s practice. Pooled data revealed higher dry matter (kg ha-1) in 150% N treatment (2465), followed by 175% N (2369)  and 125% N (2095) treatments over the farmer’s observe (1940) at active  tillering stage. However, at panicle initiation, grain filling and maturity  stages dry matter was high in 150% N treatment (5433) which was at par  with 175% N (5294), followed by 125% N (4924) treatments over the  farmers practice (4877). The panicle length (cm) showed non-significant  difference while grains panicle-1 was high in 150% N treatment (193),  followed by 175% N (182) and 125% N (176) treatments over the farmers  practice (169). In turn, it resulted in higher grain yield (kg ha-1) in 150% N  treatment (4952) which was at par with 175% N(4811) followed by 125%  N (4360) treatments over the farmers practice (3901). The straw yield (kg  ha-1) was high in 150% N treatment (6652) which was at par with 175% N treatment (6427), followed by farmers observe (5619) and 125% N  treatment (5704). Harvest index was 42.7% in 150% N treatment over the  farmer’s practice (41.0%).
Keywords: Dry seeded paddy; N-fertilizer; stuffed grains; grain yield and harvest index